Evening Chronotype and Suicide: Exploring Neuroinflammation and Psychopathological Dimensions as Possible Bridging Factors—A Narrative Review - Luca Magnani; Andrea Aguglia; Jacques Alexander; Alessandra Maiorano; Hélène Richard-Lepouriel; Sidonia Paula Iancau; Andrea Amerio; Alberto Parise; Gianluca Serafini; Mario Amore; Khoa D. Nguyen; Alessandra Costanza (Brain Sciences, 2023)
A chronotype is generally defined as the variability of the phase angle of entrainment, while the latter reflects the relationship between the timing of a certain rhythm (e.g., the sleep–wake cycle) and the timing of an external temporal cue. Individuals can be placed on a spectrum from “morning types” (M types) to “evening types” (E types). E-chronotype has been proposed as a transdiagnostic risk factor for psychiatric conditions, and it has been associated with psychopathological dimensions. Eveningness seems to be correlated with both suicidal ideation (SI) and suicidal behavior (SB) through several possible mediating factors. Immunological alterations have also been linked to later chronotypes and SI/SB. This narrative review aims to summarize the evidence supporting the possible association between chronotypes and suicide and the eventual mediating role of neuroinflammation and several psychopathological dimensions. A search of the literature (2003–2023) was conducted using various databases: PUBMED, EMBASE, Scopus, UpToDate, PsycINFO, and Cochrane Library. English-language articles were collected and screened for eligibility. Despite the apparent absence of a direct correlation between E-chronotype and suicidality, E-chronotype promotes a chain of effects that could be involved in an increased risk of SB, in which with neuroinflammation possibly plays an intriguing role and some psychopathological dimensions may stand out.